'This is men's ultimate': (Re)creating multiple masculinities in elite open Ultimate Frisbee. (June 2013) - Crocket, Hamish
Over the past 10 years, there has been an increasing focus on the complexity and diversity of masculinities produced in sporting contexts. In this article, I draw on Foucauldian notions of power and discourse to examine the performances of elite male Ultimate players. Based on a year-long ethnographic study with an elite male Ultimate team, I contribute to this growing body of literature by analyzing the performance of multiple masculinities by players within this team.